2001
DOI: 10.1161/hy1101.095995
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Strength of the Isolated Carotid Artery in SHR

Abstract: Abstract-We have previously reported an adaptation of arterial wall elasticity in spontaneously hypertensive rats (SHR) that involves an increase in both fibronectin/␣5␤1-integrin complexes and smooth-muscle elastic lamellae connections. We examined the mechanical strength (MS) of the carotid artery in relation to its elastic properties, its elastin/collagen content, and the structure of the internal elastic lamina. MS was defined as the in vitro intraluminal pressure and wall stress that produces rupture of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 34 publications
2
25
0
Order By: Relevance
“…The external diameter was measured, and dimension/ pressure and pressure/distensibility curves were constructed. 7,19,20 …”
Section: Measurement Of Arterial Compliance Ex Vivomentioning
confidence: 99%
“…The external diameter was measured, and dimension/ pressure and pressure/distensibility curves were constructed. 7,19,20 …”
Section: Measurement Of Arterial Compliance Ex Vivomentioning
confidence: 99%
“…The mechanical strength of the intact CA was characterized by determining the in vitro intraluminal pressure required to induce vascular wall rupture as described previously. 23 …”
Section: In Vivo Mechanical Propertiesmentioning
confidence: 99%
“…41 Another study identified intimal layer subfailures in rat carotid arteries under circumferential loading, although mechanics were not quantified. 11 The most appropriate methodology to identify and quantify internal layer subfailures is to open the vessel, exposing the intimal side prior to longitudinal failure testing. 54 This protocol permits synchronous identification of subfailures using videography and mechanical loading data.…”
Section: Investigation Of Vessel Mechanicsmentioning
confidence: 99%